(untitled) (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2010)
Cardiac valvulopathies may be caused by acquired or congenital diseases and result in valvular stenosis and/or insufficiency. For a correct diagnostic evaluation of cardianc valves, and in particular of rheumatic valvulopathy, pathologists should know the patient’s clinical history, the degree of insufficiency and/or stenosis and echographiacal data. Histopathologic features of rheumatic valvulopathy include precocious, tardy and terminal lesions. Rheumatic valvulopathy may produce mitral insufficiency. Mitral valve incompetence has been calssified into three types by echography (Carpentier, 1980). 56 cases of valvular samples have been examinated at our institution from January 2004 to January 2008. Any case was processed according to diagnostic/opeartive protocol we prepared carefully: gross examination, photographic documentation, sampling, standard stains and histochemical special stains. On the basis of the operative diagnostic protocol, histopathologic diagnosis of rheumatic valvulopathy was effected in three cases. Special methods of histochemistry, in addition to hematoxylin and eosin, are fundamental for the differential diagnosis of valvulopathies. Histopathologic diagnosis of rheumatic valvulopathy is complex and requests several histomorphologic data: our operative diagnostic protocol is extremely useful to reach an anatomo-pathologic diagnosis of surgical sample, which constitutes an essential element to confirm preoperative clinical-echographic diagnosis.